2019
DOI: 10.1073/pnas.1912905116
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of surface spinners in liquid metamaterials

Abstract: We show that rotating particles at the liquid–gas interface can be efficiently manipulated using the surface-wave analogue of optical lattices. Two orthogonal standing waves generate surface flows of counter-rotating half-wavelength unit cells, the liquid interface metamaterial, whose geometry is controlled by the wave phase shift. Here we demonstrate that by placing active magnetic spinners inside such metamaterials, one makes a powerful tool which allows manipulation and self-assembly of spinners, turning th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…The existence of the vertical and horizontal spin in 3D waves is also important for the motion of larger inertial particles possessing internal spin. The motion of such particles is governed by the interaction between the wave spin and particle spin, and it opens the opportunity to manipulate and sort spinning particles using structured surface waves [299]. The existence of the vertical spin in some wave configurations offers a new conceptual base for the development of the surface wave spintronics [300], where the spin of passive particles can be controlled by imposed surface waves [66].…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…The existence of the vertical and horizontal spin in 3D waves is also important for the motion of larger inertial particles possessing internal spin. The motion of such particles is governed by the interaction between the wave spin and particle spin, and it opens the opportunity to manipulate and sort spinning particles using structured surface waves [299]. The existence of the vertical spin in some wave configurations offers a new conceptual base for the development of the surface wave spintronics [300], where the spin of passive particles can be controlled by imposed surface waves [66].…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…Many studies have shown that clustering and collective motion of self-propelled particles (SPPs) are influenced by various physical factors, including the packing fraction of the SPPs, nature of the coupling between neighboring SPPs, and the type of motion of a single SPP [20,21]. Other physical factors include environmental constraints [3] such as anisotropy of the embedding fluid [22,23], geometric confinement [24][25][26][27][28][29][30][31][32][33][34][35][36] and obstacles [37,38]. An interesting effect of circular confinement, for example, is an induced vortical motion of the SPPs * Physical Review E (in press)…”
Section: Introductionmentioning
confidence: 99%
“…At microscale, i.e., at the Reynolds numbers of Re < 1, colloidal building blocks rotated using external magnetic field can be directed along user-defined paths, thus acting as colloidal microwheels ( 24 ). Recently, it was shown that water surface waves generating circular flows and polarizations ( 25 ) can efficiently interact with subwavelength spinners, which allows efficient manipulation of particles on the water surface ( 26 ). Therefore, understanding the dynamics of spinning particles in fluids constitutes a fundamental and applied problem important for physics and engineering.…”
Section: Introductionmentioning
confidence: 99%